Ready seafood: business model innovation and venturing in a mature industry - Meyer, Marc H.; Allen, Matthew; Crane, Frederick (Senate Hall, 2010)
This case describes how two brothers transform their small business from lobster harvesting, to lobster distribution: to gifting centred around fish seafood. One of the brothers, John Ready, was an entrepreneurship student in an author's class. At that time (2001), John was harvesting lobsters with his brother Brendan to pay for college tuition. By his junior year, John initiated with his brother a lobster distribution company serving the New England region. They then expanded across the United States, and then to Europe. Upon graduation in 2004, John then conceived of a direct to consumer gifting business of fresh seafood while listening to his professor talk about My M&M's from Mars, Incorporated. The innovation was not to just sell lobsters to consumers through the Web, but to use banks, law firms, and investment companies as intermediaries who would order lobsters as gifts for their high-net worth clientele. KEYWORDS: business model, innovation, entrepreneurship in a mature industry
Keywords: business model|innovation|entrepreneurship in a mature industry